Understanding Viral dsRNA-Mediated Innate Immune Responses at the Cellular Level Using a Rainbow Trout Model - Poynter, Sarah J.; DeWitte-Orr, Stephanie J. (Frontiers in Immunology, 2018)
Viruses across genome types produce long dsRNA molecules during replication (viral (v-) dsRNA). DsRNA is a potent signaling molecule and inducer of type I interferon (IFN), leading to the production of interferon-stimulated genes (ISGs), and a protective antiviral state within the cell. Research on dsRNA-induced immune responses has relied heavily on a commercially available, and biologically irrelevant dsRNA, polyinosinic:polycytidylic acid (poly I:C). Alternatively, dsRNA can be produced by in vitro transcription, (ivt-) dsRNA, with a defined sequence and length. We hypothesized that ivt-dsRNA, containing legitimate viral sequence and length, would be a more appropriate proxy for v-dsRNA, compared to poly I:C. This is the first study to investigate the effects of v-dsRNA on the innate antiviral response and to compare v-dsRNA to ivt-dsRNA induced responses in fish cells, specifically rainbow trout. Previously, class A scavenger receptors (SR-As) were found to be surface receptors for poly I:C in rainbow trout cells. In the current study, ivt-dsRNA binding was blocked by poly I:C and v-dsRNA, as well as SR-A competitive ligands, suggesting all three dsRNA molecules are recognised by SR-As. Downstream innate antiviral effects were determined by measuring IFN and ISG transcript levels using qRT-PCR and antiviral assays. Similar to what has been shown previously with ivt-dsRNA, v-dsRNA was able to induce IFN and ISG transcript production between 3h and 24h, and its effects were length dependent (ie. longer v-dsRNA produced a stronger response). Interestingly, when v-dsRNA and ivt-dsRNA were length and sequence matched both molecules induced statistically similar IFN and ISG transcript levels, which resulted in similar antiviral states against two aquatic viruses. To pursue sequence effects further, three ivt-dsRNA molecules of the same length but different sequences (including host and viral sequences) were tested for their ability to induce IFN/ISG transcripts and an antiviral state. All three induced responses similarly. This study is the first of its kind to look at the effects v-dsRNA in fish cells as well as to compare ivt-dsRNA to v-dsRNA, and suggests that ivt-dsRNA may be a good surrogate for v-dsRNA in the study of dsRNA-induced responses and potential future antiviral therapies.